Financial Accounting Fundamentals - Wild, John J. (McGraw-Hill, 2007)
Wilds Financial Accounting Fundamentals responds to the markets request for a low-cost, succinct book; a book that balances large and small businesses, and one that is contemporary, engaging, and accessible for todays students. With numerous innovative features, the author focuses on Three:Clear presentation of accounting concepts, Concise coverage to help students focus on important material, and Cutting edge technology to engage students and improve their chances for success.